Bone loss in the oestrogen‐depleted rat is not exacerbated by sitagliptin, either alone or in combination with a thiazolidinedione. Issue 10 (1st May 2013) - Cusick, T.; Mu, J.; Pennypacker, B. L.; Li, Z.; Scott, K. R.; Shen, X.; Fisher, J. E.; Langdon, R. B.; Kimmel, D. B.; Zhang, B. B.; Glantschnig, H.
Abstract : Antihyperglycaemic therapy on bone was evaluated in the ovariectomized (OVX), non‐diabetic adult rat. Animals were treated daily for 12 weeks with various doses of sitagliptin, pioglitazone, rosiglitazone, combinations of sitagliptin with pioglitazone or vehicle alone. Sitagliptin target engagement was confirmed by assessing inhibition of plasma dipeptidyl peptidase‐4 (DPP‐4) and oral glucose tolerance. Parameters related to bone health were evaluated in femur and vertebrae by dual‐energy X‐ray absorptiometry and histomorphometry. Bone mineral density (BMD) generally did not differ significantly between OVX‐sitagliptin‐treated animals and OVX‐vehicle controls. In lumbar vertebrae, however, there was significantly less BMD loss with increasing sitagliptin dose. Thiazolidinedione (TZD) treatment generally resulted in lower BMD; OVX‐TZD‐treated (but not OVX‐sitagliptin‐treated) animals also had lessened cortical thickness in central femur and profoundly greater bone marrow adiposity in lumbar vertebrae. These findings support prior findings with TZDs and suggest a neutral or beneficial impact of DPP‐4 inhibition on bone health.